The influence of basal detachment strength on formation of the southwestern Sichuan fold-thrust belt: insights from discrete-element numerical simulations - Wang, Yanqi; Wang, Lining; Ren, Rong; Wei, Guoqi; Chen, Zhuxin; Su, Nan; Zhang, Yuqing (Frontiers in Earth Science, 2023)
The southwestern Sichuan fold-thrust belt (SWSB) is a duplex detachment system and features the basal Precambrian detachment at a depth of approximately 15-17 km and the upper Mid-Triassic detachment. Moreover, the SWSB undergoes forward-breaking propagation during the Cenozoic. To date, the mechanism and kinematic evolution governing the SWSB in this thrusting deformation as well as the way the two detachments control the structural deformation pattern of the SWSB remains unknown. In this work, three discrete-element numerical models with the same strong upper detachment but basal detachments with different mechanical strengths and thicknesses were designed to study the deformation of the SWSB. The results indicate that for the Model I with a strong frictional basal detachment with thickness of 500 m, most deformation and thrust faults concentrate near the mobile backwall. Model I exhibits characteristics such as linearly increasing wedge height and stepwise increasing wedge width and slope angle. For the Model II with a modest frictional basal detachment with thickness of 500 m, the strain and deformation propagate into the foreland quickly and multiple back-thrust and thrust faults form on the upper detachment in the second thrusting period. The first thrusting period in Model II, exhibits similarities with Model I. However, in the second period, the wedge reaches a stable state, and its geometry remains constant. The geometry and activity of thrust faults in the foreland differ significantly in the model III with a modest frictional basal detachment but a greater thickness. Two additional pop-up structures are generated in the second period in this model. The first half of the first thrusting period. is similar to the first two models. In the second half of the first period and the second period, the wedge is in a stable state. In the first stage of the shortening, all models undergo a transition from a subcritical state to entering a supercritical state. The results of Model III are consistent with the deformation pattern of the SWSB. The study of the kinematics and interaction between two detachments could help hydrocarbon exploration beneath the upper detachment.